No More Wire Hangers. - Greenberg, Randi (Architectural Record, 2005)
Reports on the clothing system called Walldrobe/Wearpaper tailored by digital fabrication technologies designed by architecture professor Ben Pel. Aspect of computer-aided design and computer-aided manufacturing which caught the interest of Pel; Features of the clothing system.